Nanoparticle suspensions from carbon-rich fluid make high-grade gold deposits - Petrella, L.; Thébaud, N.; Fougerouse, Denis; Tattitch, B.; Martin, L.; Turner, S.; Suvorova, A.; Gain, S. (NATURE PORTFOLIO, 2022)
Economic gold deposits result from a 100- to 10,000-fold enrichment in gold relative to crustal background. In hydrothermal systems, this enrichment is achieved through the transport and accumulation of metals via deeply sourced fluids to a site of deposition. However, the generally low metal solubility of Au in aqueous solutions in orogenic systems requires additional processes in order to explain high-grade gold formation. Reports of Au nanoparticles in high-grade gold veins infer that their formation is linked to mineralisation. However, processes leading to nanoparticle nucleation and deposition remain poorly understood. Here we show that formation of metal nanoparticles (Au, AuAg, Cu, Ag2O) is one of the essential contributors to efficient and focused gold deposition. We report systematic and previously unrecognized metal nanoparticles preserved in amorphous silica and/or carbonic phases in five high-grade deposits. The association of metal, silica and carbonic phases helps to constrain the multiple reactive processes involved in Au, Cu and Ag metallogenesis and formation of high-grade gold mineralisation.